PERAN PERILAKU KEPEMIMPINAN WAKIL KEPALA SEKOLAH BIDANG KESISWAAN DALAM PENGORGANISASIAN SISWA BERBASIS MEDIA SOSIAL DI SMK KOTA BEKASI - Fetrimen (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Palu, 2018)
Principal leadership activities in utilizing social media can affect the effectiveness of organizing, coaching, and communication. This study discusses effective communication with students through utilizing social media. Communication through social media is done by forming groups in various social media. This research was conducted with a survey method that uses data analysis with path analysis methods where calculations are performed with the program used are Data Analysis packages found in Microsoft Excel and SPSS. The subjects of this study were the deputy principals of the Vocational High School students' field of 100 people in the city of Bekasi. The determination of the sample was taken using Slovin formula and random sampling technique, as many as 80 deputy principals in the student field were the sample of the study while 20 deputy principals in the student field were used to test the validation of the research instruments. This research is expected to contribute to society.